2012
DOI: 10.1002/cphc.201200508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Primary Alkanolamines Using an Extendable Force Field

Abstract: A classical force field is proposed for the molecular simulation of primary alkanolamines containing a NH(2)-C-C-OH backbone. A method is devised to take into account the polar (H-bonding) environment of the alkanolamines by calculating electrostatic charges in the presence of explicit solvent molecules. The force field does not use a universal set of charges, but is rather constructed by following a general method for obtaining specific charges for the different alkanolamines. The model is parameterized on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Figure displays the most frequently occurring conformers for the studied alkanolamine molecules. The dihedral angle of the MEA molecule (NCCO) was investigated in detail in previous publications ,, and is always in the gauche conformation. The conformations of the terminal hydroxyl and amine groups facilitate an intramolecular hydrogen-bond formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure displays the most frequently occurring conformers for the studied alkanolamine molecules. The dihedral angle of the MEA molecule (NCCO) was investigated in detail in previous publications ,, and is always in the gauche conformation. The conformations of the terminal hydroxyl and amine groups facilitate an intramolecular hydrogen-bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…There are many comprehensive MD studies of pure MEA that revealed a wealth of information about thermodynamics, liquid structure, and dynamic properties of liquid MEA. However, only a few simulations dealt with aqueous solutions of MEA. ,, The liquid structures of aqueous MEA solutions at different mixture compositions were investigated by Gubskaya and Orozco, diffusion coefficients were calculated by Gubskaya and da Silva, the conformer distribution for MEA at infinite dilution in water by da Silva, and a good agreement for mixed solvent densities was obtained …”
Section: Introductionmentioning
confidence: 99%
“…These behaviors are explained by the role of each substitution on the capability to induce molecular structural rearrangement, which would represent the major contribution to the enthalpy. Simond et al 5 When increasing temperature, the excess molar enthalpies become less exothermic, and the molar fraction at the minimum moves to equimolarity. Once again, according to molecular simulation, 5 the change with temperature is mainly attributed to the decrease of the strength of the intermolecular hydrogen bond simultaneously to the increase of intramolecular hydrogen bond.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of experimental data will notably improve the development of molecular simulation tools capable to describe the complex molecular interactions. 5 Excess molar enthalpy data (H E ) are useful for modeling because it is directly related to the temperature dependence of the excess Gibbs energy. Therefore, when using an activity coefficient model, excess enthalpy measurements will provide a more accurate temperature dependence for the model.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperature required for CO 2 In Figure 1 we illustrate the molecular geometry of the MEA molecule. In this paper we care-fully evaluate the accuracy of most available empirical force fields of MEA, namely MEAa2007 8 , MEAo2007 8 , MEAa2015 9 , OPLS-aa 10 , OPLS-aam 10 , GROMOS-aa 11,12 , and GROMOS-ua 11,12 .…”
Section: Classical Molecular Dynamics (Md) Is a Very Powerful Atomistmentioning
confidence: 99%